Takotsubo cardiomyopathy (Broken heart syndrome) - Manisha, Kalepu; Bhardwaj, Shruti; S.V, Sri Alekhya; P, Dhanyaswaroopa; Nallamelli, Rishitha; V.C, Randeep Raj (The Journal of Multidisciplinary Research, 2023)
Takotsubo cardiomyopathy or takotsubo syndrome (TTS), also known as stress cardiomyopathy, is a type of non-ischemic cardiomyopathy in which there is a sudden temporary weakening of the muscular portion of the heart. This condition is sometimes called “Broken Heart Syndrome”.it predominantly affects postmenopausal women, often triggered by acute emotional stressors, physical stressors, or a combination of both. The exact pathophysiological mechanisms remain incompletely elucidated. Diagnosis relies on clinical history, physical examination, ECG and cardiomyopathy from acute coronary syndrome is crucial for management.